iTRAQ-based quantitative proteomics analysis of the effect of ACT001 on non-alcoholic steatohepatitis in mice - Hui Zhou; Bin Niu; Xue Wu; Weike Chu; Yibing Zhou; Ze Chen; Yuqiang Mi; Yonggang Liu; Ping Li (Scientific Reports, 2023)
Abstract ACT001 is a novel sesquiterpene lactone derivative that has been shown to have significant antitumor and anti-inflammatory effects. However, the effect of ACT001 on nonalcoholic steatohepatitis (NASH) is unknown. Methionine and choline deficient (MCD) diet induced NASH model in C57BL/6J mice. Steatosis, inflammation and fibrosis-related indices of serum and liver tissues were detected by fully automated biochemical analyzer, enzyme-linked immunosorbent assay (ELISA) kit, flow cytometry, hematoxylin and eosin (H&E), Masson and immunohistochemical staining. The results showed that ACT001 reduced serum lipid and inflammatory factor levels, attenuated hepatic steatosis, inflammation and fibrosis, and inhibited hepatic oxidative stress and activation of NOD-like receptor protein 3 (NLRP3) inflammatory vesicles in NASH mice. In addition, 381 differentially expressed proteins (DEPs), including 162 up-regulated and 219 down-regulated proteins, were identified in the MCD group and ACT001 high-dose group using isotope labeling relative and absolute quantification (iTRAQ) technique analysis. Among these DEPs, five proteins associated with NAFLD were selected for real-time fluorescence quantitative PCR (RT-qPCR) validation, and the results were consistent with proteomics. In conclusion, ACT001 has a therapeutic effect on NASH, and the results of proteomic analysis will provide new ideas for the mechanism study of ACT001 for NASH treatment.